A road map for a domestic wind turbine manufacturing industry in Turkey - (:unkn) unknown (IGI Global, 2013)
Climate change is now widely recognized as the major environmental problem facing the globe. In large part this is due to emissions of so-called "greenhouse gases," which mainly result from the production of energy using fossil fuels. In addition to environmental problems, some countries with limited fossil fuel reserves also suffer from energy-dependency. Turkey, for instance, now imports over 90 percent of its oil and natural gas at an annual cost of approximately US$35 billion. Turkey's dependence on imported energy portends negative effects on both national security and the economy. More investment in renewable energy has thus become vital. In this context, wind energy appears not only to be the most cost-efficient, medium term solution for energy dependency, but also for global climate change mitigation. Wind energy has the potential to reduce environmental impacts because it does not generate either atmospheric contaminants or thermal pollution. It also makes economic sense because while the costs of most forms of energy are rising, the costs of wind energy are decreasing. This chapter explores the way in which a strong domestic wind turbine manufacturing industry can be nurtured in Turkey. For this purpose, the chapter focuses particularly on some key measures such as investment subsidies, tax exemptions, corporate financing schemes, and information dissemination. © 2014 by IGI Global. All rights reserved.